Pertumbuhan Ekonomi Ditinjau dari Pertumbuhan Penduduk, Tingkat Pendidikan, dan Tingkat Kemiskinan di Jawa Barat (Institut Agama Islam Negeri Kudus, 2024)
AbstractThe main indicator of the success of economic development in a region is economic growth. This research is motivated by the economic growth rate in West Java which fluctuates every year and has the highest growth rate among other provinces on the island of Java in 2022 which has never been achieved in the last 9 years. Apart from that, there are inconsistencies in the results of previous research. This research aims to determine the influence of population growth, education, and poverty on economic growth in West Java in 2014-2022. This type of research is quantitative research. This research uses panel data with samples taken using a saturated sampling technique in the form of 27 districts/cities in West Java in the form of data on economic growth, population growth, education, and poverty levels in 2014-2022, the information comes from the Central Statistics Agency in West Java. Panel data regression was chosen as a data analysis technique with the help of Eviews 12. The research results that population growth and education influence on economic growth. The poverty level did not affect economic growth in West Java Province in 2014-2022.Keywords: Population Growth; Education; Poverty; Economic Growth. AbstrakIndikator utama keberhasilan pembangunan ekonomi pada suatu wilayah adalah pertumbuhan ekonomi. Penelitian ini dilatarbelakangi oleh angka pertumbuhan ekonomi di Jawa Barat yang fluktuatif di setiap tahunnya dan memiliki angka pertumbuhan tertinggi diantara provinsi lain di Pulau Jawa pada tahun 2022 yang belum pernah dicapai dalam 9 tahun terakhir. Selain itu, terdapat ketidakkonsistenan pada hasil penelitian terdahulu. Penelitian ini memiliki tujuan guna mengetahui adanya pengaruh pertumbuhan penduduk, pendidikan, dan kemiskinan terhadap pertumbuhan ekonomi di Provinsi Jawa Barat pada tahun 2014-2022. Jenis penelitiannya adalah penelitian kuantitatif. Penelitian ini menggunakan data panel dengan penggunaan sampel diambil melalui teknik sampling jenuh berupa 27 kabupaten/kota di Jawa Barat, berupa data pertumbuhan ekonomi, pertumbuhan penduduk, tingkat pendidikan, dan tingkat kemiskinan pada tahun 2014-2022 yang informasinya berasal dari BPS Jawa Barat. Regresi data panel dipilih sebagai teknik analisis data dengan bantuan Eviews 12. Hasil penelitian bahwa pertumbuhan penduduk dan pendidikan memiliki pengaruh terhadap pertumbuhan ekonomi. Tetapi tingkat kemiskinan tidak berpengaruh terhadap pertumbuhan ekonomi di Jawa Barat tahun 2014-2022.Kata Kunci: Pertumbuhan Penduduk; Pendidikan; Kemiskinan; Pertumbuhan Ekonomi.